2021
DOI: 10.1111/cod.14004
|View full text |Cite
|
Sign up to set email alerts
|

The use of social media platforms to discuss and educate the public on allergic contact dermatitis

Abstract: Background Social media platforms are increasingly used by patients to research and discuss medical problems. Objective The aim of this study was to identify by whom, how frequently, and in what manner allergic contact dermatitis (ACD) is discussed on social media sites. Methods Search terms “allergic contact dermatitis” and “contact dermatitis” were queried across Twitter, Instagram, Reddit, Facebook, YouTube, and Google search metrics. The frequency, content, and creators of the content were assessed. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, it should be taken into account that a recent study have reported positive effects on the QoL by interdisciplinary inpatient rehabilitation measures, including patient education, that is, tertiary individual prevention, in patients with occupational hand eczema 33 . Physicians should be aware of that information about CD exist on social media platforms and are utilized and shared both by patient, physician and industry groups 34 . However, knowledge of the skin barrier and changes in lifestyle due to a contact allergy may lead to better compliance but may not necessarily lead to an improvement in life quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it should be taken into account that a recent study have reported positive effects on the QoL by interdisciplinary inpatient rehabilitation measures, including patient education, that is, tertiary individual prevention, in patients with occupational hand eczema 33 . Physicians should be aware of that information about CD exist on social media platforms and are utilized and shared both by patient, physician and industry groups 34 . However, knowledge of the skin barrier and changes in lifestyle due to a contact allergy may lead to better compliance but may not necessarily lead to an improvement in life quality.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Physicians should be aware of that information about CD exist on social media platforms and are utilized and shared both by patient, physician and industry groups. 34 However, knowledge of the skin barrier and changes in lifestyle due to a contact allergy may lead to better compliance but may not necessarily lead to an improvement in life quality. Implementing behavioural changes in the daily life of patients with CD may be seen as an extra burden to the patient.…”
Section: Discussionmentioning
confidence: 99%